Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Siswa Kelas IV - Sari, Ira; Azura, Wan; Mursida, Mursida (Paedagogie, 2026)
This study aims to measure the effectiveness of applying the Problem-Based Learning (PBL) model in improving the academic achievement of fourth-grade students in the Social Sciences (IPS) subject at Al Mutaqina Imama Private Elementary School. This research utilizes an experimental quantitative approach with a One-Group Pretest-Posttest Design. The research participants included the entire population of fourth-grade students for the 2024/2025 academic year. Data was collected using test instruments. Based on the final test results, the posttest score of the class using the problem-based learning model was 82.4, while the average score without the use of the media was 75.8. Comparative data analysis indicated a significant increase: the students' average scores rose from 75.8 (before the intervention) to 82.4 after the implementation of PBL. Hypothesis testing using SPSS v.25 yielded a Sig. (2-tailed) value of 0.000. Given that the significance value is < 0.05, the null hypothesis (Ho) is rejected, confirming that PBL has a positive and significant impact on student learning outcomes in this subject.